Improving efficiency of machining the geometrically complex shaped surfaces by milling with a fixed shift of the cutting edge - Skorkin, Anton; Kondratyuk, Oleg; Lamnauer, Nataliya; Burdeinaya, Victoria (Eastern-European Journal of Enterprise Technologies, 2019)
In order to improve efficiency of machining by milling geometrically complex shaped surfaces, mainly the methods related to improvement of properties of the tool material, change of composition and properties of the tool surface layer, application of thin film coatings, reduction of roughness of the working surfaces and improvement of operating conditions of the tool using lubricant-cooling media are mainly used. Proceeding from the above stated, scientifically grounded technical and technological solutions consisting in development of a new highly effective method for machining geometrically complex shaped surfaces by means of disk rotary cutters with a reciprocatively rocking feed motion were studied and set forth in this work. This machining method can increase the period of durability of tools by 1.7 times and milling performance by 1.6 times by means of a fixed kinematic shift of the cutting edge relative to the machined surface. A mathematical apparatus of the method of milling with a fixed shift of the cutting edge was proposed. Analysis of this method with the help of numerical functions has enabled establishment of analytical dependences for determining thickness and volume of a unit cut-off layer. Thickness of the cut-off layer is mainly affected by feed per tooth, Sz, and the angle υ influences its volume which determines normal cutting conditions. A model of distribution of heat flows in the cutting wedge for the method of milling with a reciprocatively rocking feed motion taking into consideration the amplitude of rocking motion of the workpiece was studied. A temperature decrease to 330.2...395.5 °C was established, that is by 80.6...181.6 °C for the stamp steel 9CRSI and to 193.8...285 °С, that is, by 56.6...120.2 °C for steel 45 compared to conventional milling. It was found that total length of the cutting edge increases 2.4 times with 1.5 times temperature decrease